2017
DOI: 10.3382/ps/pex240
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of indigenous chicken production systems in Rwanda

Abstract: Characterization of indigenous chicken (IC) production systems in Rwanda was conducted from November 2015 to January 2016 with the aim of understanding socio-economic characteristics, management of IC, production parameters, feed resources, and constraints faced by farmers rearing IC. A survey involving 206 households was carried out in 5 districts with the highest populations of IC using structured questionnaires. Data were analyzed using SAS software. The results showed that the majority of respondents (62.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 8 publications
19
48
1
Order By: Relevance
“…This is the good level for understanding the management and good returns for poultry production enterprise in Rwanda. This is almost similar with the report of Mahoro et al (2017). The study indicated that Easten province had 25% of household who did not receive the education level.…”
Section: Socio-economic Characteristics Of the Chickenrearing Householdssupporting
confidence: 90%
See 2 more Smart Citations
“…This is the good level for understanding the management and good returns for poultry production enterprise in Rwanda. This is almost similar with the report of Mahoro et al (2017). The study indicated that Easten province had 25% of household who did not receive the education level.…”
Section: Socio-economic Characteristics Of the Chickenrearing Householdssupporting
confidence: 90%
“…It was also found that in Kigali and South, half of the farmers were using free range, while the rest were using semi -scavenging, with minimal supplementation. This result is similar to that of Mahoro et al (2017) and Okeno et al (2012). In all provinces, the farmer reared indigenous chicken for income generation except the eastern province reported that those chicken are for home consumption.…”
Section: Socio-economic Characteristics Of the Chickenrearing Householdssupporting
confidence: 80%
See 1 more Smart Citation
“…Another challenge recorded was the paucity of information regarding the local poultry industry. Farmers have no access to information on management practices, marketing, and treatment services which is consistent with (26) where lack of information on poultry rearing was mentioned as a challenge due to lack of livestock extension services.…”
Section: Table6 Common Diseases and Parasites Listed By Farmersmentioning
confidence: 58%
“…IC production serves a critical role in the source of revenue for resource-limited countryside families [1]. The productivity of IC in Rwanda, however, is low at an average of 40 to 100 eggs per hen per year and weight ranging from 0.8 to 1.8 kg per year, which is insufficient to meet the needs of the population [2]. This setback has restricted their potential to improve the livelihoods of smallholder farmers thus failing to contribute considerably to the mitigation of poverty in rural areas.…”
Section: Introductionmentioning
confidence: 99%